The Effect Of The Implementation Of History Video Media On Students' Learning Outcomes In The Subject Of History At State Senior High School 1 Banyuasin 1 - Desky Suhendra; Supriyanto Supriyanto; SaniSafitri Safitri (Criksetra: Jurnal Pendidikan Sejarah, 2019)
This study is entitled "The Effect of Media Video Application on Student Learning Outcomes in Historical Subjects at 1 Banyuasin 1 High School." The type of research used in this study is experimental research. The formulation of the problem under study is influential or not the use of video media on the learning outcomes of students. The purpose of this study was to determine the effect of video learning media on student learning outcomes. This research was conducted on April 9 to May 14, 2018 for four meetings. This study uses two classes, namely class XI IPS 1 as an experimental class and class XI IPS 3 as a control class. The population in this study were class XI students at 1 Banyuasin Public High School 1. Determination of the study sample using Random Sampling techniques. Data collection techniques in this study were tests and observations. The variables of this study are video media (independent variables) and learning outcomes (dependent variables). The statistics used to prove the analysis hypothesis are the T test with a real level of 0.05. Based on the results of the study it is proven that there is an influence of video learning media on student learning outcomes in historical subjects in class XI of the 1 Banyuasin State Senior High School 1. This is evidenced by tcount> t table or 3.71> 1.671.